Szolgálunk és vétünk - Szobolits, Béla (Hungary : Golden Couch, 1996)
Documentary about alleged abuse committed by the police during investigations involving Roma suspects.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films